The Formulation and Evaluation of High-Fat Pellet on Lipid Profiles and Body Mass Index of Male Wistar Rats - Rosnah Rosnah; Nurpudji A. Taslim; Andi Makbul Aman; Irfan Idris; Suryani As'ad; Agussalim Buchari; Burhananuddin Bahar; Aminuddin Aminuddin; Elly Wahyudin; Gaga Irawan Nugraha (College of Pharmacy University of Baghdad, 2022)
This study aimed to explore the manufacture of high-fat pellets for obesity induction diets in male Wistar rats and determined its effect on lipid profiles and body mass index. It was an experimental laboratory method with a post-test randomized control group. Formulation of high-fat pellets (HFD) and physico-chemical characteristics of pellets were conducted in September 2019. This study used about 28 male Wistar white rats, two months old, and 150-200 g body weight. Rats were acclimatized for seven days, then divided into four groups: 7 rats were given a standard feed of Confeed PARS CP594 (P0), and three groups (P1, P2, P3) were given high-fat feed (HFD FII) 30 g/head/day. The result showed that the mean fat content of Formula II pellets (HFD FII) was higher (25.44% ± 0.16) than Formula I pellet (HFD FI) (22.55% ± 0.16) and standard feed (3%). The mean of body weight and BMI of obesity induction rat groups (P1, P2, P3) were significantly higher than the standard rat group (P0) (p <0.05). The results of the post-hoc LSD test between groups P1, P2, and P3 showed no difference in mean body weight and BMI (p> 0.05). Feed consumption in the rat fed with HFD FII pellets was higher than the standard group (P0). It means that rats preferred the HFD FII pellets. The lipid profile of the obesity induction group showed higher total cholesterol, triglycerides, and LDL, while the HDL levels were significantly lower than the standard feed group (P0). LSD post-hoc test results between P1, P2, and P3 showed no difference in the mean lipid profile (p> 0.05).  Giving HFD FII pellets, a source of fat from butter, full cream milk powder, and eggs of purebred chickens for eight weeks could make male Wistar rats obese and dyslipidemia